Endotrophin, a collagen type VI-derived matrikine, reflects the degree of renal fibrosis in patients with IgA nephropathy and in patients with ANCA-associated vasculitis - Sparding, Nadja; Genovese, Federica; Rasmussen, Daniel Guldager Kring; Karsdal, Morten Asser; Neprasova, Michaela; Maixnerova, Dita; Satrapova, Veronika; Frausova, Doubravka; Hornum, Mads; Bartonova, Lenka; Honsova, Eva; Kollar, Marek; et al. (Nephrology, dialysis, transplantation, 2022)
BACKGROUND: Renal fibrosis is the hallmark of chronic kidney disease (CKD) and is characterized by an imbalanced extracellular matrix remodelling. Endotrophin (ETP) is a signalling molecule released from collagen type VI (COL VI). ETP can be measured by the PRO-C6 assay, which quantifies the levels of COL VI formation. ETP levels were previously associated with mortality and disease progression in patients with CKD. We hypothesized that serum and urinary ETP levels correlate with the degree of interstitial fibrosis in kidney biopsies from patients with immunoglobulin A nephropathy (IgAN) and patients with anti-neutrophil cytoplasmic antibody-associated vasculitis (AAV). METHODS: We examined a cohort of 49 IgAN and 47 AAV patients. A validation cohort of 85 IgAN patients was included. ETP was measured in serum (S-ETP) and urine (U-ETP/Cr) samples, taken on the same day before renal biopsy was performed, using the enzyme-linked immunosorbent assay PRO-C6. The biopsies were evaluated for interstitial fibrosis and tubular atrophy according to the Banff and MEST-C scores. RESULTS: S-ETP and U-ETP/Cr levels correlated with kidney function, increased CKD severity, correlated with the extent of interstitial fibrosis and gradually increased with increasing degree of interstitial fibrosis and tubular atrophy. ETP outperformed the known fibrosis biomarker Dickkopf-3 for discrimination of patients with high fibrotic burden. The association of S-ETP and U-ETP/Cr with the level of kidney fibrosis was confirmed in the validation cohort. CONCLUSIONS: We demonstrated that high levels of circulating and excreted ETP are not only indicative of lower kidney function, but also reflect the burden of fibrosis in the kidneys.
Keywords: fibróza; chronická renální insuficience; Renal Insufficiency, Chronic; Atrophy; biomarkers; Glomerulonephritis, IGA; Humans; ANCA-asociované vaskulitidy; Kidney; Anti-Neutrophil Cytoplasmic Antibody-Associated Vasculitis; lidé; IgA nephropathy; Collagen Type VI; ledviny; peptidové fragmenty; IgA nefropatie; ANCA-associated vasculitis; kolagen typ VI; atrofie; Fibrosis; Peptide Fragments; chronic kidney disease; interstitial fibrosis